2015
DOI: 10.3892/etm.2015.2714
|View full text |Cite
|
Sign up to set email alerts
|

Expression of immune checkpoint molecules in endometrial carcinoma

Abstract: Abstract. The main obstacle in the development of an effective tumor vaccine is the inherent ability of tumors to evade immune responses. Tumors often use common immune mechanisms and regulators to evade the immune system. The present study aimed to analyze the expression levels of indoleamine 2,3-dioxygenase (IDO), programmed death-ligand (PD-L) 1, PD-L2, B7-H4, galectin-1 and galectin-3 in tissue samples from patients with endometrial carcinoma, in order to detect the immunosuppressive environment of endomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 41 publications
2
27
1
1
Order By: Relevance
“…Tumoral expression of PD-L1 is just one of many potential mechanisms of immune evasion, and there are little data on how the concomitant presence of other anti-immune defenses could interfere with effectiveness of anti-PD-1/ PD-L1 therapies in solid cancers, including endometrial carcinomas. Tumor expression of the immune modulatory enzyme IDO could, for instance, reduce the effectiveness of these therapies by rendering tumor-associated cytotoxic T cells dysfunctional, as exposing a tumor to immune recognition is of little utility if the immune system cannot effectively eliminate it [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumoral expression of PD-L1 is just one of many potential mechanisms of immune evasion, and there are little data on how the concomitant presence of other anti-immune defenses could interfere with effectiveness of anti-PD-1/ PD-L1 therapies in solid cancers, including endometrial carcinomas. Tumor expression of the immune modulatory enzyme IDO could, for instance, reduce the effectiveness of these therapies by rendering tumor-associated cytotoxic T cells dysfunctional, as exposing a tumor to immune recognition is of little utility if the immune system cannot effectively eliminate it [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IDO has been shown to have relevance in endometrial cancers where its expression correlates with impaired T-cell infiltration and worsened survival [16][17][18]. Work from Liu et al [14] revealed IDO expression of at least 1% in 57% of endometrial carcinomas, with significantly higher rates (63% vs. 38%, p < 0.01) in recurrent vs. primary cancers. Ino et al identified IDO expression in 49% of endometrial cancers using a cutoff of 5% tumoral expression, and found IDO was positively correlated with myometrial invasion, nodal metastasis, lymphovascular space involvement, and elevated CD3 + and CD8 + tumor-infiltrating and peritumoral lymphocytes [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the top‐10 downregulated genes, ALDH1A1 was involved in the development of uterine fibroids in an animal model indirectly . LGALS3 was related to endometrial carcinoma . TLR3 was a critical immunomodulator that played an important role in the development of gynecologic cancers .…”
Section: Resultsmentioning
confidence: 99%
“…32 LGALS3 was related to endometrial carcinoma. 33 TLR3 was a critical immunomodulator that played an important role in the development of Figure 1 Hierarchically clustered heatmap of the top 50 genes that were altered in uterine leiomyomas (UL). gynecologic cancers.…”
Section: Identification Of Differentially Expressed Genesmentioning
confidence: 99%